Emotional intelligence and its applicability to the library workplace - Cruz, Cherryl Anne L. (2002.)
"Traditional methods for measuring intelligence have always been through the use of IQ tests. Recent trends, however, are starting to favor the influence of emotional intelligence (EI) over academic intelligence in determining how successful a person will be in his personal and job performance. Emotional intelligence is the ""ability to monitor one's own and others' feelings and emotions, to discriminate among them, and to use this information to guide one's thinking and actions"". Two of the primary activities of a library organization are interacting with its users to meet their specific needs and also with people in the workplace. These activities fall under emotional intelligence. It is towards this end that this research is carried out. This study is a survey on how emotional intelligence can be applied in the library workplace. Out of the twenty eight questionnaires given, twenty three (82 percent) librarians responded c; while from the nineteen questionnaires made, ten (53 percent) ILS faculty members answered. The study concludes that the emotional competencies that the ILS professors perceive as important for librarians to have and should apply in the workplace are as follows: (In the self-awareness cluster) accurate self-assessment; awareness cluster) first, political awareness; second, leveraging diversity; and third, empathy; (In the social management cluster) first, influence; second, change catalyst; and third, conflict management, Accordingly, the librarians ranked the applicability of several emotional competencies in the library workplace as follows: (In the self-awareness cluster) first, initiative; second, innovativeness; and third, adaptability; (In the self-management cluster) first, optimism; second, initiative; and third, commitment; (In the social awareness cluster) first, political awareness; second, leveraging diversity; and third, empathy; (In the social management cluster) first, influence; second, communication; and third, conflict leadership. Furthermore, the type of position, i. e. (librarian/faculty) affects the relative level of emotional competence of the respondents' answers. In addition, the study shows that choosing which emotional competencies are needed to be applied in the library workplace is not affected by the discipline of the library where the librarians are situated in. Moreover, choosing which emotional competencies are needed in the library workplace is not affected by the gender of the respondents. However, these studies will not go far unless given particular attention is given to its application. Therefore, training programs are needed to utilize them in the library workplace. "
Vita.
Undergraduate thesis (B.L.I.S.) University of the Philippines, Diliman.
Keywords: Emotional intelligence; Librarians